Synthesis and gold-catalyzed transformations of allenic compounds - Asikainen, Martta Irmeli (2012)
This thesis is concerned with the synthesis of allenic compounds and their gold-catalyzed isomerization reactions. Its general aim is the development of new reaction methodologies within these topics and the work has been published in two separate articles. After an introductory chapter (covering relevant literature upto 2010) three separate projects are discussed: